A New Type of Ideal Convergence of Difference Sequence in Probabilistic Normed Space - Khan, Vakeel A.; Altaf, Henna; Khan, Mohammad Faisal (Communications in Mathematics and Applications, 2018)
The idea of difference sequence sets \(X(Δ)={x=(x_k):Δ xX}\) with \(X=l_∞\), \(c\) and \(c_0\) was introduced by Kizmaz [10]. Mursaleen and Mohiuddine [13] defined the idea of probabilistic normed space(PNS) and the ideal convergence in PNS. Motivated by the above two concepts, we in this paper introduce the notion of difference \(I\)-convergent sequence in PNS and study the elementary properties of this convergence.